Perioperative management of obstructive sleep apnea in lower extremity orthopedic procedures: A review of evidence to inform the development of a clinical pathway. (February 2023) - Baniak, Lynn M.; Orbell, Staci L.; Luyster, Faith S.; Henker, Richard; Strollo, Patrick J.
Abstract: Obstructive sleep apnea (OSA) is unrecognized in as high as 80% of patients before surgery. When untreated, OSA increases a surgical patient's propensity for airway collapse and sleep deprivation lending to a higher risk for emergent re-intubation, prolonged recovery time, escalation of care, hospital readmission, and longer length of stay. We have reviewed the evidence regarding diagnostic performance of OSA screening methods and the impact of perioperative management strategies on postoperative complications among patients with diagnosed or suspected OSA who are undergoing orthopedic surgery. We then integrated the data and recommendations from professional society guidelines to develop an evidence-based clinical care pathway to optimize the perioperative management of this surgical population. Successful management of patients with diagnosed or suspected OSA encompass five facets of care: screening, education, airway management, medications, and monitoring. This narrative review revealed two gaps in the evidence to inform management of patients undergoing orthopedic surgery 1) during the perioperative setting to include evidence-based interventions that reduce postoperative complications and 2) after discharge to an unmonitored environment. The clinical care pathway as well as perspectives for future research are discussed. Abstract : Obstructive sleep apnea (OSA) is unrecognized in as high as 80% of patients before surgery. When untreated, OSA increases a surgical patient's propensity for airway collapse and sleep deprivation lending to a higher risk for emergent re-intubation, prolonged recovery time, escalation of care, hospital readmission, and longer length of stay. We have reviewed the evidence regarding diagnostic performance of OSA screening methods and the impact of perioperative management strategies on postoperative complications among patients with diagnosed or suspected OSA who are undergoing orthopedic surgery. We then integrated the data and recommendations from professional society guidelines to develop an evidence-based clinical care pathway to optimize the perioperative management of this surgical population. Successful management of patients with diagnosed or suspected OSA encompass five facets of care: screening, education, airway management, medications, and monitoring. This narrative review revealed two gaps in the evidence to inform management of patients undergoing orthopedic surgery 1) during the perioperative setting to include evidence-based interventions that reduce postoperative complications and 2) after discharge to an unmonitored environment. The clinical care pathway as well as perspectives for future research are discussed.